Effect of nicotine patches in pregnancy on infant and maternal outcomes at 2 years: follow-up from the randomised, double-blind, placebo-controlled SNAP trial - Cooper, Sue; Taggar, Jaspal; Lewis, Sarah; Marlow, Neil; Dickinson, Anne; Whitemore, Rachel; Coleman, Tim (Elsevier, 2014)
BACKGROUND: The SNAP (Smoking and Nicotine in Pregnancy) trial compared nicotine replacement therapy (NRT) patches with placebo in pregnant smokers; although NRT doubled cessation rates in the first 4 weeks, by delivery no differences in maternal smoking or birth outcomes were noted. As a result, NRT used in standard doses during pregnancy is considered ineffective for smoking cessation. Subsequent effects of NRT on the children of treated mothers are unknown because no trials have investigated the effect of gestational NRT use beyond birth. To assess whether NRT use in pregnancy might cause harm to infants, we aimed to compare effects of NRT and placebo on infant development 2 years after delivery. METHODS: 1050 pregnant smokers aged 16-45 years, at 12-24 weeks' gestation, and smoking at least five cigarettes per day were recruited from seven hospitals in England between May 1, 2007, and Feb 26, 2010, and followed up until their infants were 2 years old. Participants were randomly assigned (1:1) to receive up to 8-weeks treatment with NRT (15 mg/16 h transdermal patches) or identically packaged and visually matched placebo patches (all patches manufactured by and purchased at market rate from United Pharmaceuticals, Amman, Jordan), issued as two 4-week supplies (521 for NRT group, 529 for placebo group) [Corrected]. Randomisation was stratified by site with participants, health-care professionals, and research staff masked to treatment allocation. The primary results for participants and infants at delivery were published in 2012; we present results from the trial cohort 2 years after birth. After delivery, questionnaires were posted to participants and, if there was no response, to family physicians. The primary outcome at 2 years was infants' survival without developmental impairment (ie, no disability or problems with behaviour or development). Treatment groups were compared on an intention-to-treat basis. The trial is registered with Controlled-Trials.com, number ISRCTN07249128. FINDINGS: Questionnaires were returned at 2 years for 891 (88%) of 1010 live singleton births (445 of (88%) 503 given NRT and 446 (88%) of 507 given placebo). Because of missing data, developmental outcomes, including four infant deaths, were documented for 888 of (88%) 1010 singleton infants; 445 (88%) of 503 infants in NRT group and 443 (87%) of 507 infants in placebo. In the NRT group, 323 (73%) of 445 infants had no impairment compared with 290 (65%) of 443 infants in the placebo group (odds ratio [OR] 1.40, 95% CI 1.05-1.86, p=0.023). At 2 years, 15 (3%) of 521 mothers in the NRT group and nine (2%) of 529 mothers in the placebo groups self-reported prolonged smoking abstinence since a quit date set in pregnancy (OR 1.71, 95% CI 0.74-3.94, p=0.20). Adverse events were not collected after delivery, but previously reported adverse pregnancy and birth outcomes were similar in the two groups. INTERPRETATION: Infants born to women who used NRT for smoking cessation in pregnancy were more likely to have unimpaired development. NRT had no effect on prolonged abstinence from smoking but did cause a temporary doubling of smoking cessation shortly after randomisation during pregnancy, which could explain findings. If findings are confirmed by subsequent research, this has potential implications for the management of smoking in pregnancy. FUNDING: National Institute for Health Research Health Technology Assessment Programme.